Foreign Exchange Rates: Legal Aspects and the Management and Minimization of Risk - Manóvil, Rafael (Revue générale de droit, 1989)
The profitability of an international economical contract is directly linked to the currency determined in it and to the risks of potential foreign exchange variations. The length of the contract and the political and economical stability of the concerned country define the magnitude of the risk. The author explains various means available to the contracting parties to minimize the currency risk: taking into consideration Argentina, in many ways an unstable country, he explains the elements that must be taken into account for the selection of the payment currency and the drafting of the contract.He then itemizes the clauses that can be inserted in a contract so as to insure that it will be effectively executed in the determined currency while underlining that many of these clauses do not have any effect due to the legislation of certain countries.